Analyses of Adverse Drug Reactions–Nationwide Active Surveillance Network: Canadian Pharmacogenomics Network for Drug Safety Database. (19th November 2018) - Tanoshima, Reo; Khan, Amna; Biala, Agnieszka K.; Trueman, Jessica N.; Drögemöller, Britt I.; Wright, Galen E. B.; Hasbullah, Jafar S.; Groeneweg, Gabriella S. S.; Ross, Colin J. D.; Carleton, Bruce C.; ,
Abstract: Adverse drug reactions (ADRs) are a major problem in modern medicine, representing up to the fourth‐highest cause of mortality. Pharmacogenomic tests are 1 of the most promising methods to tackle the challenge of ADRs. The objective of this study was to analyze the clinical and demographic information of the pan‐Canadian active surveillance network, Canadian Pharmacogenomics Network for Drug Safety (CPNDS). Information entered into the database by trained active surveillors between May 15, 2005 and May 9, 2017 was collected and analyzed. Specific data included for analysis were number of ADR reports, reports of drug use without ADRs, date of onset of ADR, suspected drugs, concomitant drugs, and fatal ADR cases. The CPNDS database consisted of 93, 974 reports of medication use, including 10, 475 reports of ADRs, of which 72.6% occurred in pediatric patients (≤21 years old). Self‐reported ancestries were predominantly Europe (38.2%), Canada (9.6%), and East Asia (4.9%). The 5 most frequent ADRs were cutaneous ADRs, peripheral neuropathy, cardiotoxicity, central nervous system toxicity, and ototoxicity. The 5 drugs most commonly suspected to cause ADRs were methotrexate, vincristine, doxorubicin, cisplatin, and L‐asparaginase. The CPNDS database is a valuable resource to identify clinical and genomic predictors of ADRs. The database also highlights our candidate ADRs for pharmacogenomic discovery research to identify additional ADR biomarkers. Additionally, the database provides information that can be used for developing strategies to prevent ADRs and raises awareness of ADRs among Canadian healthcare professionals.